2010
DOI: 10.1111/j.1464-410x.2010.09765.x
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐term evaluation of the transobturator male sling for post‐prostatectomy incontinence: focus on prognostic factors

Abstract: • The clinical outcome was evaluated according to pad use and the Patient Global Impression of Improvement scale and by assessment of side effects. 'Cure' was defined as no pad usage and 'improvement' as a decrease in pad use by > 50%.• Factors related to functional outcome were studied by univariate and multivariate analysis. RESULTS• After a mean ± SD (range) follow-up of 21 ± 6 (12-36) months, 62% of patients were cured, 16% improved and 22% not improved.• Failure (no cure or improvement) was associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
113
4
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(129 citation statements)
references
References 14 publications
2
113
4
2
Order By: Relevance
“…In accordance with the present data; Cornu, recently presented durable results after a mean follow-up of 21 months, confirming that the AdVance® sling is an efficient treatment option also in the mid-term. The mentioned study showed slightly lower success rates than the present study (no improvement in 22 vs. 11.5% of patients), but interestingly, Cornu also found a trend for an association with previous radiation therapy and treatment failure (16). Bauer and coworkers as well demonstrated a high success rate of the AdVance® sling of 51.6% cured and 23.8% improved patients after thelve months.…”
Section: Discussioncontrasting
confidence: 50%
“…In accordance with the present data; Cornu, recently presented durable results after a mean follow-up of 21 months, confirming that the AdVance® sling is an efficient treatment option also in the mid-term. The mentioned study showed slightly lower success rates than the present study (no improvement in 22 vs. 11.5% of patients), but interestingly, Cornu also found a trend for an association with previous radiation therapy and treatment failure (16). Bauer and coworkers as well demonstrated a high success rate of the AdVance® sling of 51.6% cured and 23.8% improved patients after thelve months.…”
Section: Discussioncontrasting
confidence: 50%
“…Several studies have evaluated outcomes after AdVance implantation, and, currently, data up to a maximum follow-up of 39 months are available [12][13][14][15][16][17][18]. The AdVanceXP was marketed in 2010 and its innovations aim to improve both surgical implantation and postoperative stability.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no influence of patients' age on the outcome and complication rates could be identified in MS [14,18,19] or AUS [7] . In this regard, our results are consistent with the present literature of AUS and MS.…”
Section: Discussionmentioning
confidence: 99%
“…Various prospective studies of MS exclude prior urethral strictures [14,22] . Cornu et al [19] investigated a more heterogenic population with the AdVance sling and identified prior urethral stricture disease as independent predictor for failure. Further research has to evaluate under which conditions stricture disease may compromise the continence outcome of MS.…”
Section: Discussionmentioning
confidence: 99%